2019
DOI: 10.1055/a-0821-5653
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Rheum Turkestanicum in Hexachlorobutadien-Induced Renal Toxicity

Abstract: Hexachlorobutadien is nephrotoxic agent in rodents. The mechanism of toxicity includes generation of free radicals, depletion of thiol groups and production of toxic metabolites. Antioxidant compounds may reduce HCBD-nephrotoxicity. In this research we investigated the effect of Rheum turkeatanicum extract against HCBD-toxicity. The animals were divided to 4 groups which were including control (saline, 1 mL/kg), HCBD (100 mg/kg) and treatment groups which received extract at doses 100 and 200 mg/kg. The extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
(26 reference statements)
2
5
0
Order By: Relevance
“…The R. turkestanicum extract could restore these parameters, which was in agreement with antioxidant and hepatoprotective effects of this plant reported by other studies [9,12,35]. Also, there are reports that protective effects of R. turkestanicum against organ toxicity induced by doxorubicin [36], gentamicin [37], HgCl 2 [38], and hexachlorobutadiene [37] is mediated through its antioxidant activity.…”
Section: Discussionsupporting
confidence: 90%
“…The R. turkestanicum extract could restore these parameters, which was in agreement with antioxidant and hepatoprotective effects of this plant reported by other studies [9,12,35]. Also, there are reports that protective effects of R. turkestanicum against organ toxicity induced by doxorubicin [36], gentamicin [37], HgCl 2 [38], and hexachlorobutadiene [37] is mediated through its antioxidant activity.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, previous research has also reported that doxorubicin elevates ALT ( Barakat et al, 2018 ); our findings support these previous ones of doxorubicin-induced clinical enzyme alterations. Our findings also support that R. turkestanicum protects against doxorubicin-induced cardiotoxicity by restoring cellular antioxidant defenses and as an antioxidant in various cells and toxicity models ( Hosseini et al, 2018 ; Boroushaki et al, 2019a ; Boroushaki et al, 2019b ; Hosseini et al, 2020 ). The protection by the plant is also associated with improvements in LDH and creatinine phosphokinase activities ( Hosseini et al, 2017 ; Hossini et al, 2022 ).…”
Section: Discussionsupporting
confidence: 81%
“…R. turkestanicum reduced doxorubicin-induced toxicity in cardiomyocytes (H9C2 cells),[ 12 ] glutamate toxicity in PC12 cells. [ 18 ] The protective effects of this herb against toxic agents such as gentamicin,[ 14 ] mercuric chloride,[ 15 ] hexachlorbutadien,[ 16 ] and cisplatin[ 13 ] have been also demonstrated. Another study showed that R.turkestanicum prevented cardiac injury following STZ-induced diabetic in rats via attenuation of lactate dehydrogenase and creatine phosphokinase.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] Recent studies have revealed a protective effect of this plant against toxic agents, such as doxorubicin,[ 12 ] cisplatin,[ 13 ] gentamicin,[ 14 ] mercuric chloride,[ 15 ] and hexachlorobutadien. [ 16 ] Antioxidant activity of some plants of Rheum genus has been attributed to the presence of bioactive components that scavenge free radicals (IC 50 value in DPPH assay: 2.8-11.8 μM). [ 17 ] R. turkestanicum counter acted hexachloro butadien and mercuric chloride-induced nephrotoxicity through its antioxidant properties indicated by attenuated lipid peroxidation and increased total thiol content.…”
Section: Introductionmentioning
confidence: 99%